The lost history of Christianity : the thousand-year golden age of the church in the Middle East, Africa, and Asia- and how it died - Jenkins, Philip, 1952- (Harper One, 2008)
A lost history revealing that, for centuries, Christianity's center was actually in the Middle East, Asia, and Africa, with significant communities extending as far as China.